Stereotactic radiofrequency ablation of subcardiac hepatocellular carcinoma: a case-control study - Peter Schullian (International Journal of Hyperthermia, 2019)
Purpose: The purpose of this study is to evaluate the safety and efficacy of stereotactic radiofrequency ablation (SRFA) for the treatment of subcardiac hepatocellular carcinoma (HCC). Material and methods: From 2003 to 2018, 79 consecutive patients underwent 104 multi-probe SRFA sessions for the treatment of 114 subcardiac HCC with a median size of 2.5 cm (0.5–9.5 cm). The results were compared with a randomly selected control group of 79 patients with 242 HCC with a median size of 2.0 cm (0.5–12 cm) following SRFA in other (non-subcardiac) locations with propensity score matching. Results: The 95.6% of the tumors were successfully treated by the first ablation session (primary technical efficacy rate) and 99.1% after the second session (secondary technical efficacy rate). Local tumor recurrence developed in 8 nodules (7.0%). Major complication and perioperative mortality rates were 7.7% (8/104) and 1% (1/104), respectively. The overall survival (OS) rates from the date of the first SRFA with single subcardiac HCCs were 92%, 77% and 65% at 1, 3 and 5 years, respectively, with a median OS of 90.6 months. The disease-free survival (DFS) after SRFA was 75, 34 and 34%, at 1, 3 and 5 years, respectively, with a median DFS of 19.1 months. There was no statistically significant difference with the control group in terms of local tumor control, safety, OS and DFS. Conclusion: SRFA of subcardiac tumors is as safe and efficacious as when treating tumors remote from the heart.